The Other Europe: Identity Problems of Central Europe (Politeja, 2018)
Philosophers in Central Europe are highly dependent on the Western European tradition of philosophy, while politicians in the region tend to use arguments that are often foreign to the ones used in Western Europe. The philosophical tradition of Central Europe is dependent on Western European tradition – it would be impossible to speak about any kind of distinct regional philosophical paradigm. The situation with political self‑understanding in the region is very different. The politicians in the region are aware of the various differences between the two cultural and political traditions. Today these differences have become especially clear in various disagreements between politicians from the Visegrád Group and their colleagues in Western Europe. Politicians from Central Europe propose their own understanding of the meaning of Western civilization. This phenomenon can be described as a new political Messianism. The old Messianims of the 19th century today are being replaced by new consciousness of the specific mission of the region. Conservative politicians propose an understanding of the region which is based on cultural differences from Western Europe. Various conceptions about the singular identity of the region that were developed in the ninth decade of the 20th century by Czesław Miłosz, Milan Kundera and György Konràd today are gaining a new political significance.